Literasi dan Inklusi Keuangan sebagai Faktor Penentu Minat Investasi di Kalangan Pekerja Migran Indonesia - Sri Lestari Pujiastuti; Imas Maesaroh; Andriyansah Andriyansah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
The increasing deployment of Indonesian migrant workers (PMI) to various destination countries, especially in Asia and Africa, has generated substantial income inflows for families back home. However, low financial literacy, limited access to formal financial services, and a tendency toward short-term consumption often undermine this economic potential. This study investigates financial literacy and inclusion's influence on investment interest among Indonesian migrant workers. Utilizing a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 200 respondents through an OECD-adapted questionnaire covering financial knowledge, behavior, attitudes, and service accessibility. The findings indicate that financial literacy significantly affects investment interest (? = 0.386; p = 0.013), suggesting that enhanced financial competence increases the propensity to invest. Similarly, financial inclusion also exerts a significant positive influence (? = 0.351; p = 0.030), revealing that improved access to financial products and services, such as savings, insurance, and digital investment platforms, encourages migrant workers to engage in productive financial activities. These results highlight the importance of targeted financial education programs and inclusive financial infrastructures to strengthen the long-term economic resilience of returning migrant workers and their families. Future research should explore additional moderating variables such as digital platform adoption, migration duration, and sociocultural dynamics to enrich the understanding of investment behavior within this demographic.